The level of perceptions toward agriculture land development programme among Orang Asli in Pahang, Malaysia - Hamid, Halilah; Abu Samah, Asnarulkhadi; Man, Norsida (Canadian Center of Science and Education, 2013)
In Malaysia, the government has embarked a diverse and comprehensive development programmes in efforts to develop the life of Orang Asli, the indigenous community in peninsular Malaysia. These programmes include providing budget allocation for houses for the hardcore poor, financial savings scheme, basic amenities and community infrastructure and plantation. Agriculture Land Development Programme (ALDP) was claimed by the Department of Orang Asli Development (JAKOA) as main Department activities in an effort to eradicate poverty among the Orang Asli community. The ALDP is still emphasizing in 10th Malaysia Plan as the main tool to address the high incidence of poverty among Orang Asli and certain budget was allocated for this programme. One of the factors that can influence the successful rate of development programme is participant’s perception. Therefore, the objective of this study is to determine the level of perception of Orang Asli toward ALDP oil palm plantation. This is a quantitative descriptive study whereby data were gathered using a questionnaire. Data was analysed using the SPSS for descriptive and correlation analysis involved 170 respondents. Overall, the finding shows that the level of perception is moderate. Some recommendations were made due to results of study in order to improve the ALDP in future.